2016
DOI: 10.1111/fcsr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Brand Personality, Consumer Satisfaction, and Loyalty: A Perspective from Denim Jeans Brands

Abstract: This study employed Aaker's brand personality framework to empirically investigate the personality of denim jeans brands and to examine the impact of brand personality on consumer satisfaction and brand loyalty based on data collected from 474 college students. Results revealed that the personality of denim jeans brands can be described in six dimensions with 51 personality traits: attractiveness, practicality, ruggedness, flexibility, friendliness, and honesty. The results indicated that consumers associate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 57 publications
(166 reference statements)
1
34
2
3
Order By: Relevance
“…Using the survey method in Beijing, results indicated an affirmative link amid consumer's brand trust in food producers and retailers with their perceptions of food safety. When marketers aim to increase specific trust, they should address the integrity and ability of producers [70]. Drescher et al [71] studied Canadian households' perceptions of processed meat and their levels of trust.…”
Section: Brand Trustmentioning
confidence: 99%
“…Using the survey method in Beijing, results indicated an affirmative link amid consumer's brand trust in food producers and retailers with their perceptions of food safety. When marketers aim to increase specific trust, they should address the integrity and ability of producers [70]. Drescher et al [71] studied Canadian households' perceptions of processed meat and their levels of trust.…”
Section: Brand Trustmentioning
confidence: 99%
“…Customer loyalty is a strategic objective for companies and the heart of marketing efforts, due to its positive impact on profitability and sustainability over time (Evanschitzky et al, 2011;Flavián et al, 2006;Nisar & Whitehead, 2016;Su & Tong, 2016). Previous studies have shown that the relative costs of customer retention are substantially less than those of acquisition (Flint et al, 2011;Fornell & Wernerfelt, 1987;Oliver, 1999), and firms spend dramatically to build and manage customer loyalty (Watson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Companies should continue to focus on factors that lead to customer loyalty and retention. Attitudinal loyalty and repurchase intention are important measures for customer loyalty and retention, which are crucial to a company's long-term business success and financial performance (Su & Tong, 2016). For a company to achieve long-term success, it is essential that it understands the factors affecting attitudinal loyalty and repurchase intention and act on it accordingly.…”
Section: Discussionmentioning
confidence: 99%